2022
DOI: 10.1155/2022/3331119
|View full text |Cite|
|
Sign up to set email alerts
|

Fibroblast Growth Factor 3 Is Associated with Tongue Squamous Cell Carcinoma: A Controlled Study

Abstract: Objective. To explore the effects of fibroblast growth factor 3 (FGF3) on the proliferation, cell cycle, and apoptosis of the tongue squamous cell carcinoma SCC-9 cell line (SCC-9). Methods. We measured the proliferation of SCC-9 cells in a control group, an FGF3 intervention group, and a fibroblast growth factor (FGFR) inhibitor intervention group in cholecystokinin octapeptide (CCK-8) experiments. We studied effects of FGF3 on the cell cycle and apoptosis of tongue cancer cells using flow cytometry. We furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%